Close reading: What is reading for?. Issue 3 (27th May 2019) - Eppley, Karen
Abstract: Close reading has been a key shift in classroom instruction under the Common Core State Standards (CCSS). The CCSS positions evidence extraction as the purpose for reading in school and is clear that close reading is the means by which this should occur. Using alternate readings of the picture book, Letting Swift River Go, I'll argue for the importance of reading with critical place consciousness while offering a critique of close reading as the only authorized textual approach within the CCSS. While close reading advocates point to its pedagogical potential, neglected in these discussions are questions about the broader purposes of learning to read in school. Despite the intuitive appeal of close reading, considering the practice through critical place consciousness suggests it is an inadequate construction of what reading is and what reading can do. To make this argument, I offer two readings of Letting Swift River Go, a close reading and a place-conscious reading, and conclude with a discussion about the implications of reading with a sole focus on what lies within the four corners of a text.